2020
DOI: 10.3390/jcm9040898
|View full text |Cite
|
Sign up to set email alerts
|

Primary Retention of Molars and RANKL Signaling Alteration during Craniofacial Growth

Abstract: The primary retention of molars observed in clinic corresponds to a still-unexplained absence of molar eruption despite the presence of an eruption pathway, resembling the experimental transient inhibition of RANKL signaling in mice. The aim of the present study was to confront the hypothesis according to which the primary retention of molars is associated with transitory perturbations to RANKL signaling during growth as part of a wider craniofacial skeleton pattern. The experimental strategy was based on comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Transitory alteration to RANKL functions during the initial stage of dental root elongation and tooth eruption have also been reported in mouse models of PFE 21 …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Transitory alteration to RANKL functions during the initial stage of dental root elongation and tooth eruption have also been reported in mouse models of PFE 21 …”
Section: Introductionmentioning
confidence: 78%
“…19,20 Transitory alteration to RANKL functions during the initial stage of dental root elongation and tooth eruption have also been reported in mouse models of PFE. 21 Indepth analysis of chronological regulation and spatial localization of genes is key for improved understanding. Also, validation of the protein expression is essential for derivation of therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Although using of traditional exams such as a lateral X-ray (cephalometric analyzes) may allow the identification of NPC [ 13 ], 2D imaging could not provide complete visualization of the size and position of the canal, as previously reported [ 14 ]. Thus, we classified NPC shapes by using CBCT sagittal cross section, according to Mardinger and coworkers [ 40 ], and confirmed that the most represented NPC shape was funnel (34.59%), followed by cylindrical (28.57%), and hourglass (24.81%), while the banana type was observed only in 12.03% participants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Uesugi and coworkers [ 12 ] reported that CBCT may be useful for simulating the post-treatment position of the maxillary incisors and NPC in order to provide safe teeth movement. On the other hand, using lateral cephalogram, the position of NPC could also be evaluated [ 13 ], although CBCT provides more detailed information about NPC such as morphology and morphometric characteristics [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,13,14,15,16 Transitory alteration to RANKL functions during the initial stage of dental root elongation and tooth eruption have also been reported in mouse models of PFE. 17 In-depth analysis of chronological regulation and spatial localization of genes is key for improved understanding. Also, validation of the protein expression is essential for derivation of therapeutic interventions.…”
Section: Pathogenesis Of Pfementioning
confidence: 99%